2021
DOI: 10.1007/s00394-021-02555-7
|View full text |Cite
|
Sign up to set email alerts
|

Age and time trends of dairy intake among children and adolescents of the DONALD study

Abstract: Purpose To describe age and time trends in dietary intake of Total Dairy (TD) (g/1000 kcal Total Energy Intake) and types of dairy (weight percent of total dairy intake, w%TD) represented as Low Fat Dairy (LFD), High Sugar Dairy (HSD), Fermented Dairy (FD) and Liquid Dairy (LD) among children and adolescents in Germany. Methods Overall, 10,333 3-day dietary records kept between 1985 and 2019 by 1275 DONALD participants (3.5–18.5 years; boys: 50.8%) were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
(72 reference statements)
2
15
0
Order By: Relevance
“…A limitation of the present study is the overrepresentation of families with a high socio-economic status in the collective of the DONALD study, which limits the generalisability of our results [ 15 ]. However, in our previously conducted trend analysis with the same sample, the dairy intake data were comparable to the results of the German National Nutrition Survey (NVS II) [ 10 , 36 ]. Furthermore, we cannot rule out the possibility of underreporting.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…A limitation of the present study is the overrepresentation of families with a high socio-economic status in the collective of the DONALD study, which limits the generalisability of our results [ 15 ]. However, in our previously conducted trend analysis with the same sample, the dairy intake data were comparable to the results of the German National Nutrition Survey (NVS II) [ 10 , 36 ]. Furthermore, we cannot rule out the possibility of underreporting.…”
Section: Discussionsupporting
confidence: 66%
“…Conflicting effects were observed in overweight children. Previous trend analyses with DONALD participants showed a fluctuating trend in the intake of HSD over time [ 10 , 30 ]. Nevertheless, the intake of low-sugar varieties should be recommended, as the intake of free sugars in Germany exceeds the limit of 10% of energy intake [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the cause of excess weight is multifactorial, changes in diet and decreased level of physical activity have been proposed as contributing factors to the obesity epidemic [1]. Evidence suggests a decrease in dairy consumption coincides with the rise in obesity prevalence in pediatric population [2]. A large percentage of children do not consume the recommended amounts of low-fat and fat-free dairy products, fruits, vegetables, and whole grains, which results in low intakes of calcium, potassium, fiber, magnesium, and vitamin E [3].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the differences in study design, one plausible explanation behind the observed discrepancies could be attributed to the differences in composition (fat/sugar content), processing type (i.e., fermentation), and form (liquid/solid) of the studied dairy products (i.e., milk, cheese, and yoghurt) [ 11 ]. In light of the conflicting evidence, the fact that Greek children have been recognised as among the most obese in Europe, the forecasted increasing trends of dairy product consumption in Greece, as well as the fundamental role of dairies on musculoskeletal health, and the global burden of childhood obesity, the aim of the present study was to investigate the association of the type of milk with weight status through several characteristics in a representative sample of Greek preadolescent students aged 10–12.…”
Section: Introductionmentioning
confidence: 99%